La universalidad del espacio de Urysohn y su grupo de isometrías (2017)
"To study the universality of the Urysohn space with respect to the separable metric spaces, to use the tools of theory of the models as the limits of Frayse and the use of types. Likewise, the universality of its group of isomerries was studied with respect to the topological second accounting groups, using the construction proposed by M. Katetov in 1986." -- Tomado del Formato de Documento de Grado.